The causal association between smoking initiation, alcohol and coffee consumption, and women’s reproductive health: A two-sample Mendelian randomization analysis - Jiang, Zhaoying; He, Renke; Wu, Haiyan; Yu, Jiaen; Zhu, Kejing; Luo, Qinyu; Liu, Xueying; Pan, Jiexue; Huang, Hefeng (Frontiers in Genetics, 2023)
Objective: A number of epidemiological studies have demonstrated smoking initiation, alcohol and coffee consumption were closely related to women's reproductive health. However, there was still insufficient evidence supporting their direct causality effect. Methods: We utilized two-sample Mendelian randomization (TSMR) analysis with summary datasets from genome-wide association studies (GWAS) to investigate the causal relationship between smoking initiation, alcohol and coffee consumption and women's reproductive health related traits. Exposure genetic instruments were variants significantly related to traits. The inverse-variance weighted (IVW) method was used as the main analysis approach, and we also performed MR-PRESSO, MR-Egger, weighted median and weighted mode to supplement sensitivity test. Then, the horizonal pleiotropy was detected by using MRE intercept and MR-PRESSO methods, and the heterogeneity was assessed by Cochran’s Q statistics. Results: We found evidence that smoking women had a significant inverse causal association with the sex hormone-binding globulin (SHBG) levels (corrected β = -0.033, P=9.05E-06) and age at menopause (corrected β = -0.477, P= 6.60E-09), a potential positive correlation of the total testosterone (TT) levels (corrected β = 0.033, P=1.01E-02). In addition, there was suggestive evidence for the alcohol drinking effect on the elevated TT levels (corrected β = 0.117, P= 5.93E-03) and earlier age at menopause (corrected β = -0.502, P=4.14E-02) among women. While coffee consumption might decrease the female SHBG levels (corrected β = -0.034, P = 1.33E-03). Conclusion: Our findings suggested that smoking in women significantly decreased their SHBG concentration, promoted earlier menopause, and possibly reduced the TT levels. Alcohol drinking had a potential effect on female higher TT levels and earlier menopause, while coffee consumption might lead to lower female SHBG levels.